Aortoesophageal and aortobronchial fistula caused by Candida albicans after thoracic endovascular aortic repair - Končar, Igor B; Dragaš, Marko; Sabljak, Predrag; Peško, Predrag; Marković, Miroslav; Lazar, Davidović (Vojnosanitetski pregled, 2017)
Introduction. Endovascular stent-graft placement has emerged as a minimally invasive alternative to open surgery for the treatment of aortic aneurysms and dissections. There are few reports on stent graft infections and aortoenteric fistula after endovascular thoracic aortic aneurysm repair, and the first multicentric study (Italian survey) showed the incidence of about 2%. Case report. We presented a 69-year-old male patient admitted to our hospital 9 months after thoracic endovascular aortic repair, due to severe chest pain in the left hemithorax and arm refractory to analgesic therapy. Multislice computed tomography (MSCT) showed a collection between the stent graft and the esophagus with thin layers of gas while gastroendoscopy showed visible blood jet 28 cm from incisive teeth. Surgical treatment was performed in collaboration of two teams (esophageal and vascular surgical team). After explantation of the stent graft and in situ reconstruction by using Dacron graft subsequent esophagectomy and graft omentoplasty were made. After almost four weeks patient developed hemoptisia as a sign of aortobronchial fistula. Treatment with implantation of another aortic cuff of 26 mm was performed. The patient was discharged to the regional center with negative blood culture, normal inflammatory parameters and respiratory function. Three months later the patient suffered deterioration with the severe weight loss and pneumonia caused by Candida albicans and unfortunately died. The survival time from the surgical treatment of aortoesophageal fistula was 4 months. Conclusion. Even if endovascular repair of thoracic aortic diseases improves early results, risk of infection should not be forgotten. Postoperative respiratory deterioration and finally hemoptisia could be the symptoms of another fistula.
Keywords: aortic aneurysm; thoracic; surgical procedures; minimally invasive; stents; postoperative complications; reoperation; candida albicans